Fertility in female cancer survivors: a systematic review and meta-analysis. Issue 1 (July 2020) - Busnelli, Andrea; Vitagliano, Amerigo; Mensi, Laura; Acerboni, Stefano; Bulfoni, Alessandro; Filippi, Francesca; Somigliana, Edgardo
Abstract: Data on the effects of cancer treatments on fertility are conflicting. The aim of the present systematic review and meta-analysis was to determine the chances of childbirth in women survivors of different types of cancer. PubMed, MEDLINE, Embase and Scopus were searched from database inception to 17 July 2019 for published cohort, case-control and cross-sectional studies that investigated the reproductive chances in women survivors of different cancer types. Random-effects models were used to pool childbirth hazard ratios, relative risks, rate ratios and odds ratios, and 95% confidence intervals were estimated; 18 eligible studies were identified. Childbirth chances were significantly reduced in women with a history of bone cancer (HR 0.86, 95% CI 0.77 to 0.97; I 2  = 0%; P  = 0.02 (two studies); RaR 0.76, 95% CI 0.61 to 0.95; I 2  = 69%; P  = 0.01 (two studies); breast cancer (HR 0.74, 95% CI 0.61 to 0.90 (one study); RaR 0.51, 95% CI 0.47 to 0.57; I 2  = 0%; P < 0.00001 (two studies); brain cancer (HR 0.61, 95% CI 0.51 to 0.72; I 2  = 14%; P < 0.00001 (three studies); RR 0.62, 95% CI 0.42 to 0.91 (one study); RaR 0.44, 95% CI 0.33 to 0.60; I 2  = 95%; P < 0.00001 (four studies); OR 0.49, 95% CI 0.40 to 0.60 (one study); and kidney cancer (RR 0.66, 95% CI 0.43 to 0.98 (one study); RaR 0.69, 95% CI 0.61 to 0.78 (one study). Reproductive chances in women survivors of non-Hodgkin's lymphoma, melanoma and thyroid cancer were unaffected. Women with a history of bone, breast, brain or kidney cancer have reduced chances of childbirth. Thyroid cancer, melanoma and non-Hodgkin's lymphoma survivors can be reassured.